Clinical spectrum of yellow phosphorous poisoning in a tertiary care centre in South India: a case series. (July 2017) - Mishra, Ajay Kumar; Devakiruba, Nathaniel Samson; Jasmine, Sudha; Sathyendra, Sowmya; Zachariah, Anand; Iyadurai, Ramya
Rodenticides such as yellow phosphorus are highly toxic compounds which are commonly used for pest control. Reports of yellow phosphorus poisoning from tropical nations is scanty. In this retrospective study, we report the clinical features, mortality and predictors of mortality among nine patients at a tertiary care centre in south India. Yellow phosphorus consumption was common among a younger age group of patients. The mean duration of presentation after consumption was five days. The most common clinical manifestations seen were abdominal pain and vomiting followed by a depressed sensorium. Features of acute liver failure including coagulopathy were seen in all patients. Despite all patients receiving supportive therapy, a poor outcome or death resulted in the majority. Early referral to a tertiary care centre, meticulous monitoring and supportive measures are key elements of patient management as there are no specific antidotes available at present. Increase in public and physician awareness to the toxin and implementation of preventive policies is of utmost importance.